PENERAPAN DATA MINING UNTUK MENENTUKAN PEMBERIAN BANTUAN KELOMPOK TANI MENGGUNAKAN ALGORITMA C.50 PADA DINAS PERKEBUNAN SUMATERA UTARA - Saut P Tamba; Jodi Daniel Pransisko Manalu; Villa Delfya Sarumaha; Erika Girsang; Verli Vernando S Colia; Putra Edi Mujahid (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
The Plantation Service is an implementing element of the regional autonomy of the Provincial Government led by a head of service who is domiciled under and responsible to the governor through the regional secretary. The duties of the plantation office include carrying out the function of formulating policies in the fields of plantation production, plantation protection, farming, plantation business facilities, licensing implementation, guidance, assistance in the plantation sector. The plantation office is ready to grow young agricultural entrepreneurs by providing business capital assistance to the community and farmer groups every year. With the existence of farmer group capital assistance, it will create more young farmers who will change the image of farmers, farmer group assistance is one of the activities in order to realize the regeneration of farmers designed for the development, skills, and entrepreneurial spirit of the younger generation in agriculture. problems that occur in providing farmer group assistance, one of which is still the provision of assistance that is not on target, causing the provision of assistance not to people who need help, so that the utilization of this assistance is not optimal. In addition, the provision of assistance is done manually, making it less efficient in any way. To overcome these problems, a system is needed that can help assess real and objective prospective beneficiaries. This assessment uses calculations based on the criteria for prospective beneficiaries with the highest ranking system. In this system, the calculation is done using datamining with the C5.0 algorithm. In testing the methods and algorithms in this study, it produces a decision tree with the first root of information and technology services, then the next root is bookkeeping administration, then the last rood is routine meetings. With the root, researchers can decide which farmer groups receive assistance. the results of the decision tree are implemented into the RStudio programming language.